The evolution of the genus triticum as an economic cereal - Fitz, L. A. (My University, 1902)
Introduction: The study of our cereals is a most fascinating subject, and, apart from the intense interest which necessarily attaches to that cereal from whence comes our “staff of life”, the study of the history and development of the grain and of the operations necessary for its successful cultivation, the subsequent treatment in mill and bake-house, provides us with a series of intellectual problems of the highest interest. The peculiarities of the growth of the plant, the characteristics of the different types, the creation of new varieties, the unique chemical nature of the grain, the problems connected with soil and climate, the question of storing and transport, together with a study of the diseases and insect enemies that attack plant and grain, one and all furnish material sufficient for the study of a life-time. In treating such a broad subject I shall be able to touch in only the briefest possible manner the multitude of subjects herein presented for our study. The principal cereal belonging to the genus Triticum that we are especially interested in, and the one that will be most discussed here, is Triticum sativum vulgare, or wheat. This cereal is the principal grain food of civilized communities, and next to rice, the principal grain food of mankind. Its cultivation is of the very greatest antiquity, it being cultivated even in prehistoric times, as were also rice and barley. Spelt, which is a small grained variety of wheat, has been found in the lake-dwellings of Switzerland, human habitations which have been traced back to the stone age.
Citation: Fitz, L. A. The evolution of the genus triticum as an economic cereal. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Triticum; Triticum Sativum Vulgare; Wheat; Cereal; Historical Development; Grain Science; Cultivation; Theses